Report on the Icelandic school system - International Conference on Education, 38th, Geneva, 1981; Iceland. Ministry of Culture and Education (Ministry of Culture and Education, 1981)
Incl. bibl. Official report from Iceland for the 1981 ICE on educational organization. Educational innovations, research and development are also described in detail. Innovative efforts have been focused on curriculum development for the comprehensive primary school and reorganization of the secondary education system. A new bill has been introduced in Parliament concerning the development of comprehensive secondary schools, aiming at providing students with general education as well as preparation for further study or vocational training. A description of teacher education, adult education, and comments on the ICE recommendations are given. A bibliography is included